Transmission electron microscopic studies on the granular leukocytes of guinea fowl (Numida meleagris) - GUPTA, VARSHA; SINGH, ISHWAR (The Indian Journal of Animal Sciences, 2011)
The blood cells from 10 guinea fowls were used for ultrastructural studies of granulocytes. It was observed that the cytoplasm of heterophils was laden with pleomorphic membrane bound 5 types of granules. The number of elongated rod shaped granules was more than the other types. The cytoplasmic granules of eosinophils were rounded in shape. Some granules were having vacuoles in the center. The basophils had 4 types of the granules in the cytoplasm.Â